Importância do médico veterinário na prevenção e controle da COVID-19. - Aquino, Vanessa Alves (2021)
On January 30, 2020, the World Health Organization (WHO) declared that the outbreak of the disease caused by the new coronavirus (SARS-CoV-2) was a public health emergency of international importance, which led to the promotion of scientific and public policy adaptations among countries. In this sense, a greater participation of multidisciplinary teams is reviewed to contribute to preventive measures and to control the spread of Covid-19. As a component of public health, the veterinarian through the effectiveness of a single health perspective, stood out in the performance and elucidation of questions about the etiologic investigation of the virus as well as in the participation of actions on health education. Through integrative literature review, a theoretical discussion is traced in order to report the actions of the veterinarian. As a result, when considering the concept of single health that refers to the inseparability between human health, animal health and environmental health, this professional is duly able to act in the face of a pandemic scenario, especially Covid-19.